JUVENILE MYOCLONIC EPILEPSY: FOCUS ON THE USE OF TOPIRAMATE (LITERATURE REVIEW AND OWN DATA) - K. Yu. Mukhin; O. A. Pylaeva (Русский журнал детской неврологии)
Juvenile myoclonic epilepsy (JME) is an inherited genetic syndrome within the group of idiopathic generalized epilepsies (IGE). The disease is characterized by an adolescence-onset with massive myoclonic seizures often combined with generalized convulsive seizures and absence seizures and by typical changes in the electroencephalogram appearing as short generalized polyspike-and-wave epileptiform discharges with a frequency of 3–6 Hz. Despite the high rate of remission (75–85 %) in patients receiving adequate therapy, this form of epilepsy brings more significant inconveniences for patients than many other forms of IGE. Such factors as violation of sleep hygiene, missing the doses of antiepileptic drugs (AED) or discontinuing the therapy cause recurrence of seizures in the vast majority of patients with JME, even in those with long-term remission. Due to the high recurrence rate in patients with JME, the treatment is usually lengthy; thus, the issues of its efficacy and tolerability, as well as the choice of starting therapy are particularly important in the case of JME. The impact of AED on the reproductive functions in women is a subject of major concern, since the active period of the disease and antiepileptic therapy covers the adult (and often adolescent) age.Valproic acid was widely used for treatment of JME, but now this drug is prescribed less frequently (especially in girls and women) due to the possible negative impact on reproductive function and its teratogenic effect. So, choosing an alternative drug with high efficacy and tolerability is crucial for patients with JME. The authors present their own experience of JME treatment with topiramate. Our results suggest that topiramate is a highly effective well-tolerated drug that can be used for JME therapy without a significant impact on the reproductive functions in female patients.